A scoping review on the links between sustainable development goal 14 and early childhood caries - Morenike Oluwatoyin Folayan; Imen Ayouni; Arthemon Nguweneza; Ola Barakat Al-Batayneh; Jorma I. Virtanen; Balgis Gaffar; Duangporn Duangthip; Ivy Guo Fang Sun; Nneka Kate Onyejaka; Hamideh Daryanavard; Tshepiso Mfolo; Carlos A. Feldens; et al. (BMC, 2023)
Abstract Background The Sustainable Development Goal (SDG) 14 addresses life below the waters, an important source of protein and contributor to global food security and economic development. Our aim was to explore possible evidence on the links between life below water and early childhood caries (ECC). Methods This scoping review identified articles on the link between life below water and caries according to the PRISMA-ScR guidelines. Three electronic databases (PubMed, Web of Science, and Scopus) were systematically searched in January 2023, using specific search terms. Studies written in English, with full text available, addressing life under water, focusing on dental caries in humans, with results that can be extrapolated to control ECC in children less than 6 years of age were included in the review. Descriptive statistics were used to summarize the retrieved papers and graphical presentation was used for visualization. Results There were 224 publications retrieved of which 13 studies, published between 1960 and 2022, were included in the analysis. The papers originated from Asia (7/13), North America (3/13), Europe (1/13), and 2/13 had multi-country authorship. Also, four laboratory studies extracted agents from marine products to determine their efficacy in preventing caries formation and preventing/slowing plaque formation; four letters discussed the caries prevention potential of sea salt as a source of fluoride; and two review articles about the positive effects of extracted marine products for caries prevention. Most (11/13) studies addressed target 14.1 concerned with enriching the marine environment with nutrients and minerals; two addressed target 14.4 focused on ensuring fish stocks are within biologically sustainable levels; two addressed target 14.7 aimed at increasing the economic benefits through sustainable use of marine resources such as fisheries; and one focused on target 14.5 aimed at conserving marine areas by increasing protected areas. In addition, one ecological study assessed the association between the ecosystem and ECC. Conclusions Currently, there is little known about the impact of protection of marine and coastal ecosystem from pollution and ocean acidification on the risk of ECC. Further evidence on possible associations between life below water and ECC management is needed.